Mina Tani Mask Dance: Javanese Cultural Character Education (Catharsis, 2022)
The Mina Tani Mask Dance is one of the content at the Pandu Dance Studio, the Mina Tani Mask dance represents an identity or characteristic that comes from elements in Pati district. Mina Tani Mask Dance is a new Creation Dance which is of the mask dance type and describes the social, economic and cultural conditions of the community which is packaged into a form of dance, namely the Mina Tani Mask dance. This research aims to analyze the integration of Character Education in the learning process of the Mina Tani Mask Dance at the Pandu Dance Studio, Pati Regency, which includes the character and behavior of noble Javanese culture. The research uses qualitative method in a descriptive form and a research approach in the form of an interdisciplinary approach. The data sources are used in this research is 4P which means person, place, process, and paper. The data collection techniques use observation, interview, and documentation technique. The data is obtained by descriptive analysis. The results of the research show that the Education of Ethics in Mina Tani Mask Dance at the Pandu Dance Studio, Pati Regency gives attention and applies social ethics that is based on manners that have a role in society or socializing, namely on the basis of the noble moral teachings of Javanese culture.